Studi Pengaruh Temperatur Kalsinasi dalam Pembentukan Nanomagnetite dengan Metode Green Synthesis Ekstrak Daun Nanas - Putra Parmita, Ade Wahyu Yusariarta; Panji; Dewanto, Hizkia Alpha; Sasongko, Ashadi; Qulub, Fitriyatul; Triana, Yunita; Parmita, Ade Wahyu Yusariarta Putra (LPPM ITK, 2023)
In synthesizing Fe3O4 nanoparticles using the green synthesis method by adding FeCl3.6H2O and pineapple leaf extract. Pineapple leaf extract is used as a natural reducing agent which contains hydroxyl and carbonyl, which acts as a reducing agent for the synthesized FeCl3.6H2O. Then after the precipitate is obtained, calcination will be carried out, where the calcination temperature in the synthesis becomes a factor in forming Fe3O4 nanoparticles. Different calcination temperatures of 400°C, 450°C, and 500°C were given to prepare Fe3O4 nanoparticles, with the XRD test results confirming that Fe3O4 nanoparticles were formed. In the SEM-EDX test, the optimum variation is 400°C because the average particle size is 150.23 nm with irregular particle shapes. Then proceed with the SAA results with a surface area of 60.125 m²/g. Nanomagnetite produced by green synthesis of pineapple leaf extract can be used as a removal dyes.